(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Outsourcing is a faculty where companies can pass on their secondary activities to specialized companies, focusing their business objectives on the main activities. However, outsourcing reflects the work relationship, which is why this article aims to analyze the phenomenon of outsourcing, within the scope of the labor relationship. And also to study the historical evolution, the conceptualization and the type of contract of outsourcing, through doctrinal approach .. In addition to analyzing labor responsibility. And finally the new law of outsourcing in Brazil X convention of the ILO (International Labor Organization). Keywords: Outsourcing; Service Borrower; Labor Responsibility; Labor Law; ILO.